Um mecanismo baseado em sensibilidade à situação para otimizar a transmissão de dados de aplicações de sensoriamento urbano - Rolim, Carlos O.; Rossetto, Anubis G.; Leithardt, Valderi R. Q.; Borges, Guilherme A.; dos Santos, Tatiana F. M.; Souza, Adriano M.; Geyer, Claudio F. R. (Anais do Simpósio Brasileiro de Computação Ubíqua e Pervasiva (SBCUP), 2016)
One challenge in urban sensing applications is related to the transmission of data when network infrastructure is intermittent or unavailable. For such task, the Opportunistic Networks emerged as a promising alternative. The main problem in this context is how to improve messages routing between network nodes. Thus, this work presents a engine that employs situation awareness in conjunction with uncertainty treatment to overcome such limitation. The experiments demonstrate that the proposed engine was an acceptable performance and can be used as a basis for opportunistic data transmission in a urban sensing architecture called UrboSenti.